Pendampingan Pembuatan Demplot Nanas dan Sayuran di Distrik Taroi, Kabupaten Teluk Bintuni, Papua Barat - Ishak Musaad; Obadja Andris Fenetiruma; Inna Marta Rumainum; Ratna Ningsi; Amelia Samin Sarungallo (Institut Pertanian Bogor, 2026)
The mentoring activity for establishing pineapple and vegetable demonstration plots (demplots) in Taroi District, Teluk Bintuni Regency, is a collaborative effort between the Tangguh LNG Bintuni company and the University of Papua (UNIPA). This program is designed to enhance the knowledge, skills, and motivation for gardening among Taroi residents, enabling them to produce vegetables and pineapples as new economically valuable income sources. The activities were conducted across four villages: Taroi, Tambanewa, Pera-pera, and Sorondouni. The commodities used in the demonstration plots were pineapple, chili, upland kangkong (water spinach), and mustard greens. The methodology employed was a participatory approach, including surveys, interviews, training, and pre-test/post-test evaluations. The implementation consisted of five main stages: site survey, Focus Group Discussions (FGD), participant selection, preparation of tools and materials, establishment of the demonstration plots, and activity evaluation. The results indicated that the majority of the Taroi District community resides in coastal areas with relatively thick peat soil conditions. Consequently, the local residents generally had little interest in planting vegetables, except for pineapple, which was grown with minimal maintenance. Findings also showed that prior to the mentoring, 59% of participants did not know how to control pests and diseases (OPT), 25% used pesticides, 8% removed diseased plants, and 8% regularly weeded. Only a small number of participants recognized the importance of limiting seeds per planting hole (27.27%), the importance of nurseries (28.57%), and types of fertilizers (42.86%). After the mentoring sessions, the participants' knowledge and skills increased to 100%. Furthermore, 84% of participants agreed with the implementation of this activity, and 76.92% agreed that the program provides long-term benefits for the community.